P-140 Developing a strategy for a research active hospice – process and progress. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Radcliffe, Christina; Hewison, Alistair; Talbot, Deborah
Abstract : Background: If evidence-based care is to be provided for patients at the end of life, hospices must engage in research. A framework has been developed which provides guidance for three levels of research participation which hospices can use to become Research Active. The production of this guidance coincided with the Hospice securing funding to support the achievement of one of its core strategic aims to: "promote, encourage or assist research into the care and treatment of people suffering from [chronic or terminal] illnesses." Aims: To develop an inclusive and realistic research strategy for the hospice To increase research activity in the hospice To build a partnership approach involving key stakeholders Approach: A palliative care consultant was designated as a 'Research Champion' and recruited to provide two protected research sessions a week. In addition a senior lecturer was supported by the local University to work with the hospice to develop research. They devised a research strategy which guided the development of research activity in the hospice. Outcomes: The strategy was endorsed by the Hospice Board and several short term objectives were achieved including: re-establishing a journal club to promote scholarship and research; reviewing the research dissemination and promotion function; reviewing existing research to ensure it was reported widely; and integrating research into the business planning cycle. In the medium term, the aim is to integrate research activity with the University by supporting staff to undertake academic work, and strengthening the links with existing research teams and recruit a research nurse to join the team. The hospice has already become research active, with involvement in several portfolio clinical trials. Conclusion: Through investment in research and the development of a research strategy considerable progress has been made. Work continues to increase research activity in the longer term.